Ecotin-Like ISP of L. major Promastigotes Fine-Tunes Macrophage Phagocytosis by Limiting the Pericellular Release of Bradykinin from Surface-Bound Kininogens: A Survival Strategy Based on the Silencing of Proinflammatory G-Protein Coupled Kinin B2 and B1 Receptors. (10th September 2014) - Svensjö, Erik; Nogueira de Almeida, Larissa; Vellasco, Lucas; Juliano, Luiz; Scharfstein, Julio
Abstract : Inhibitors of serine peptidases (ISPs) expressed by Leishmania major enhance intracellular parasitism in macrophages by targeting neutrophil elastase (NE), a serine protease that couples phagocytosis to the prooxidative TLR4 /PKR pathway. Here we investigated the functional interplay between ISP-expressing L. major and the kallikrein-kinin system (KKS). Enzymatic assays showed that NE inhibitor or recombinant ISP-2 inhibited KKS activation in human plasma activated by dextran sulfate. Intravital microscopy in the hamster cheek pouch showed that topically applied L. major promastigotes (WT and Δ i s p 2 / 3 mutants) potently induced plasma leakage through the activation of bradykinin B2 receptors (B2 R). Next, using mAbs against kininogen domains, we showed that these BK-precursor proteins are sequestered by L. major promastigotes, being expressed at higher % in the Δ i s p 2 / 3 mutant population. Strikingly, analysis of the role of kinin pathway in the phagocytic uptake of L. major revealed that antagonists of B2 R or B1 R reversed the upregulated uptake of Δ i s p 2 / 3 mutants without inhibiting macrophage internalization of WT L. major . Collectively, our results suggest that L. major ISP-2 fine-tunes macrophage phagocytosis by inhibiting the pericellular release of proinflammatory kinins from surface bound kininogens. Ongoing studies should clarify whether L. major ISP-2 subverts TLR4 /PKR-dependent prooxidative responses of macrophages by preventing activation of G-protein coupled B2 R/B1 R.